2012
DOI: 10.1002/cjoc.201200657
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite Nanotubes, a Multifunctional Nanovehicle for Anticancer Drug Delivery

Abstract: Targeted drug delivery systems have attracted a great deal of interest by virtue of their potential use in chemotherapy. In this study, multicomponent halloysite nanotubes (HNTs) have been evaluated as a platform to assist and direct the delivery of anticancer drug doxorubicin (DOX) into cancer cells. Folic acid (FA) and magnetite nanoparticles were successfully grafted onto HNTs via amide reaction whereas the drug has been introduced by capitalizing electrostatic interaction between cationic drug and anionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 44 publications
2
34
0
1
Order By: Relevance
“…The negative external surface was attributed to varying external and internal composition (SiO 2 and Al 2 O 3 , correspondingly) (Levis and Deasy, 2002;Guo et al, 2012). Zeta potential results shown in Table 2 demonstrated that zeta potential of nanotubes containing GABA were in the range of -25 mV and -32 mV.…”
Section: Characterization Of Hntsmentioning
confidence: 85%
See 2 more Smart Citations
“…The negative external surface was attributed to varying external and internal composition (SiO 2 and Al 2 O 3 , correspondingly) (Levis and Deasy, 2002;Guo et al, 2012). Zeta potential results shown in Table 2 demonstrated that zeta potential of nanotubes containing GABA were in the range of -25 mV and -32 mV.…”
Section: Characterization Of Hntsmentioning
confidence: 85%
“…Time-dependent release profiles of GABA from different nanotube formulations presented in Figure 5 demonstrated sustained release in PBS (pH 7.4) (Guo et al, 2012). Prolonged release of GABA was ascribed to the release of lumen loaded GABA of which the diffusion was substantially retarded by the onedimensional nanotube structure of HNT (Tan et al, 2014).…”
Section: In Vitro Drug Releasementioning
confidence: 98%
See 1 more Smart Citation
“…HNTs Anti-câncer [23] Ibuprofeno [24] Resveratrol [25] Tetraciclina [26] Benzitriazol [27] Dexametasona [28] Mesalazina [29] Dexametasona, Furosemida e Nefedipina [30] Dialtizem [31] Haloisita modificada com 3-aminopropiltrietoxissilano Ibuprofeno [32] Adesivo modificado de HNTs para uso odontológico Doxiciclina [33] HNTs modificado com sal de triazol Curcumina [34] Compósito de HNTs e materiais biocompatíveis (hialuronato de sódio com polimetacrilato de hidroxietil) para formação de hidrogel 5-fluoracila (5-FU) [35] HNTs modificado com antisurvivina tRNA Fármacos de atividade antitumoral [36] HNTs em microesferas porosas Dopamina; Lacase [37] HNTs modificado com 3-aminopropiltrietoxsilano Aspirina [38] HNTs modificado com ciclodextrinas (unidas aos nanotubos) Curcumina [34] HNTs com ativação básica da estrutura Ofloxacino [39] Compósito de HNTs e poli-ácido lático-co-glicólico (PLGA) Tetraciclina [40,41,42] Nanocompósitos HNTs, grânulos de alginato de sódio e hidroxiapatita para formação de hidrogel Diclofenaco de sódio [43] Microesferas de quitosana, Fe 3 O 4 e HNTs Ofloxacino [44] DNA-envolto em HNTs Doxirrubicina [45] HNTs enxertado com ácido fólico e magnetita Doxirrubicina [46] Compósito de HNTs com polimetilmetacrilato (PMMA) formando cimento ósseo para a substituição de quadril e joelho Sulfato de gentamicina [47] Compósito de HNTs com álcool polivinílico, montmorilonita, metacrilato de polimetila formando filmes Tetraciclina [48] Pellets com HNTs e celulose microcristalina Fentanil [49] Fonte: Arquivos do autor, 2015.…”
Section: Forma Utilizada Fármaco Referênciaunclassified
“…A very recent in-vivo toxicity study in a soil nematode Caenorhabditis elegans has also demonstrated high safety prospects of this novel clay even at high concentration of 1000 g/mL [17]. Various studies have shown drug delivery and biological potential of this nanotubular material through in-vitro experiments, yet none has examine cytotoxicity from the perspective of oral drug delivery systems [8,13,[18][19][20].…”
Section: Introductionmentioning
confidence: 95%